Hydroalcoholic leaves extract of Vaccinium ashei Reade promotes cell cycle arrest and apoptosis on T-cell acute lymphoblastic leukemia. Issue 17 (1st September 2022) - Meneghetti, Dalila; Cezarotto, Verciane Schneider; do Nascimento, Natália Paiva; Migita, Natacha Azussa; Corrêa, Juliana Ronchi; Riccio, Maria Francesca; Zambaldi, Lilian Girotto; Yunes, José Andrés; Artico, Leonardo Luís
Abstract: Vaccinium ashei Reade, popularly known as Rabbiteye blueberry, has several therapeutic properties attributed to the phenolic compounds present in its leaves and fruits. Here, we sought to evaluate the effects of the hydroalcoholic extract from V. ashei leaves (Bluegem cultivar, VAB) in T-cell Acute lymphoblastic leukemia (T-ALL). The VAB extract was toxic to T-ALL cells at the ∼60 µg/ml concentration. T-ALL cell death occurred through apoptosis. VAB extract was found to induce micronuclei formation, p53 pathway activation, and cell cycle arrest. Those mutagenic effects were evidenced through microscopy analysis and molecular p53 pathway activation. A series of phenolic compounds were identified in VAB extract by mass spectrometry, such as vanillic acid, catechin, caffeic acid, chlorogenic acid, rutin, coumaric acid, taxifolin, quercetin and naringenin, some of which are presumed to induce DNA damage. In conclusion, the V. ashei leaves extract may have important secondary metabolites with antileukemic properties. Graphical Abstract: UF0001